Small and scattered: poor law children's homes in Leeds, 1900–1950. (2nd September 2017) - Cottam, Susan
Abstract : By the turn of the twentieth century, the concepts of home and family had begun to have a positive influence on institutional life. Within poor law circles, large, residential institutions became seen as inappropriate for the needs of children without family support, and moves were made to transfer them into smaller, family-sized units of care. Cottage homes were one option, and, less commonly, scattered homes. This article argues that it was scattered homes that held the greatest potential to create a homely, family-orientated environment, and its adoption by the Leeds Poor Law Guardians in Leeds placed them in the vanguard of best practice at the beginning of the twentieth century with regard to the care of children. At the twentieth century's mid-point, the local authority in Leeds continued to favour the same system.